Effects of increasing standardized ileal digestible lysine during gestation on reproductive performance and modeled requirements in gilts and sows from a commercial production system - Thomas, Lori Lynn (Kansas State University, 2019)
A study was conducted to determine the effects of standardized ileal digestible (SID) lysine (Lys) during gestation on reproductive performance of gilts and sows and effects on piglet birthweight. These data were used to model changes in protein deposition and estimate SID Lys requirements. A total of 936 females were allotted to 1 of 4 dietary treatments (SID Lys intake of 11, 13.5, 16, and 18.5 g/d) on d 5 of gestation. Gilts and sows received 5.3 and 5.8 Mcal NE/d and their respective Lys intake throughout the entire gestation period. Initial BW and backfat were obtained on d 4 of gestation while final BW and backfat were obtained on d 111. Piglet BW was obtained within 12 h of birth. Gestation was divided into 3 stages: d 5 to 39 (early), 40 to 74 (mid), and 75 to 108 (late). Final BW at d 111 of gestation increased (linear, P < 0.001) for gilts and sows as SID Lys increased. There was no evidence for differences in final backfat depth. The percentage of pigs born alive increased (P = 0.006) with increasing SID Lys intake for sows, but not gilts as a result of a treatment by parity group interaction (P = 0.043) for percentage stillborn pigs. In gilts, there was no evidence for differences among treatments in the percentage stillborn pigs but in sows, as dietary SID Lys intake increased, the probability of a pig born as a stillborn decreased (linear, P = 0.002). Increasing SID Lys intake during gestation did not affect total born or born alive piglet birthweight. These results suggest that increasing SID Lys intake in gestation increased female BW, without changing backfat depth, suggesting BW gain was in the form of protein and not lipid accretion. To validate this hypothesis, Lys utilization was modeled using daily intake and BW values. The model follows the principle that energy is partitioned between maintenance, growth of conceptus, and maternal protein and lipid deposition. Requirements for SID Lys were estimated based on whole body protein deposition. Regardless of parity group or stage of gestation, as SID Lys increased, whole body protein deposition increased (linear, P < 0.001). For gilts and sows, whole body protein deposition increased (P < 0.05) in each sequential stage of gestation. Whole body protein deposition was greater for gilts (P < 0.05) in each stage of gestation, compared to sows. Estimated SID Lys balance (intake - requirement) increased with increasing SID Lys (quadratic, P < 0.054), and decreased (P < 0.05) in each sequential stage of gestation for both gilts and sows. Sow SID Lys balance was greater throughout gestation compared to gilts (P < 0.05). Overall, the model shows changes in protein retention of the conceptus and maternal protein deposition differ by parity and stage of gestation. Based on predicted changes in protein deposition, providing females with 13.5 g/d SID Lys adequately meets Lys requirements and ensures gilts do not go into a negative Lys balance at any time during gestation.
Keywords: Gilt; Sow; Gestation; Lysine requirement; Reproduction